-2(3S-5)-10=-3(9S+3)-4

Simple and best practice solution for -2(3S-5)-10=-3(9S+3)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(3S-5)-10=-3(9S+3)-4 equation:


Simplifying
-2(3S + -5) + -10 = -3(9S + 3) + -4

Reorder the terms:
-2(-5 + 3S) + -10 = -3(9S + 3) + -4
(-5 * -2 + 3S * -2) + -10 = -3(9S + 3) + -4
(10 + -6S) + -10 = -3(9S + 3) + -4

Reorder the terms:
10 + -10 + -6S = -3(9S + 3) + -4

Combine like terms: 10 + -10 = 0
0 + -6S = -3(9S + 3) + -4
-6S = -3(9S + 3) + -4

Reorder the terms:
-6S = -3(3 + 9S) + -4
-6S = (3 * -3 + 9S * -3) + -4
-6S = (-9 + -27S) + -4

Reorder the terms:
-6S = -9 + -4 + -27S

Combine like terms: -9 + -4 = -13
-6S = -13 + -27S

Solving
-6S = -13 + -27S

Solving for variable 'S'.

Move all terms containing S to the left, all other terms to the right.

Add '27S' to each side of the equation.
-6S + 27S = -13 + -27S + 27S

Combine like terms: -6S + 27S = 21S
21S = -13 + -27S + 27S

Combine like terms: -27S + 27S = 0
21S = -13 + 0
21S = -13

Divide each side by '21'.
S = -0.619047619

Simplifying
S = -0.619047619

See similar equations:

| y=5x^2-45x+100 | | 3w^2-2w+2=0 | | 8x+28-8x=28 | | 42=2/3x | | 7x-1=9x-15 | | X/12-46=6 | | -6u+46=6u | | x-(0.2x)=0.6 | | 5/3u=25 | | -(5X+4)-(-4X-9)=13 | | 12y^2+23y+5= | | 9v^2-30+25=0 | | 4+9k=-5 | | 6w-2=2w+58 | | 9v^2-30v-25=0 | | 8x=16/7 | | D=26/pi | | http://media1.acellus.com/Library/00001022_223_A1.gif | | 56+8m=128 | | 4y^2+17y-15= | | 14y+1=1y+27 | | n-17=-13 | | 17n-70=168 | | 8x-10=8x-6 | | 42=4x+2x | | 4a+1=1a+25 | | f(x)=0.15x+5 | | 8y-5y=27 | | 5/3x-1=6/5x | | 6(x+30)=90 | | 8z-6=58 | | 5z+5=40 |

Equations solver categories